High‐Impact Mechanical Loading Increases Bone Material Strength in Postmenopausal Women—A 3‐Month Intervention Study. (27th April 2018) - Sundh, Daniel; Nilsson, Martin; Zoulakis, Michail; Pasco, Courtney; Yilmaz, Melis; Kazakia, Galateia J; Hellgren, Martin; Lorentzon, Mattias
ABSTRACT: Bone adapts to loading in several ways, including redistributing bone mass and altered geometry and microarchitecture. Because of previous methodological limitations, it is not known how the bone material strength is affected by mechanical loading in humans. The aim of this study was to investigate the effect of a 3‐month unilateral high‐impact exercise program on bone material properties and microarchitecture in healthy postmenopausal women. A total of 20 healthy and inactive postmenopausal women (aged 55.6 ± 2.3 years [mean ± SD]) were included and asked to perform an exercise program of daily one‐legged jumps (with incremental number, from 3×10 to 4×20 jumps/d) during 3 months. All participants were asked to register their performed jumps in a structured daily diary. The participants chose one leg as the intervention leg and the other leg was used as control. The operators were blinded to the participant's choice of leg for intervention. The predefined primary outcome was change in bone material strength index (BMSi), measured at the mid tibia with a handheld reference probe indentation instrument (OsteoProbe). Bone microstructure, geometry, and density were measured with high‐resolution peripheral quantitative computed tomography (XtremeCT) at the ultradistal and at 14% of the tibia bone length (distal). Differences were analyzed by related samples Wilcoxon signed rank test. The overall compliance to the jumping program was 93.6%. Relative to the control leg, BMSi of the intervention leg increased 7% or 0.89 SD ( p  = 0.046), but no differences were found for any of the XtremeCT‐derived bone parameters. In conclusion, a unilateral high‐impact loading program increased BMSi in postmenopausal women rapidly without affecting bone microstructure, geometry, or density, indicating that intense mechanical loading has the ability to rapidly improve bone material properties before changes in bone mass or structure. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.